Author Correction: Plasma Electrolytic Oxidation as a Feasible Surface Treatment for Biomedical Applications: an in vivo study (Scientific Reports, (2020), 10, 1, (10000), 10.1038/s41598-020-65289-2) - Polo, Tárik Ocon Braga [UNESP]; Silva, William Phillip Pereira [UNESP]; Momesso, Gustavo Antonio Correa [UNESP]; Lima-Neto, Tiburtino José [UNESP]; Barbosa, Stéfany [UNESP]; Cordeiro, Jairo Matozinho; Hassumi, Jaqueline Suemi [UNESP]; da Cruz, Nilson Cristino [UNESP]; Okamoto, Roberta [UNESP]; Barão, Valentim A. R.; Faverani, Leonardo P. [UNESP] (Springer Nature, 2020)
The original version of this Article contained errors in the spelling of the authors Tárik Ocon Braga Polo and William Phillip Pereira Silva which were incorrectly given as Tárik Okon Braga Polo and William Phillip da Silva respectively.